Channeling commercial fund to NGO-MFIs: a case study of Bank-NGO linkage programme of Sonali Bank - Rahman, Md. Mukhlesur (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master of Development Studies, 2004.